2017
DOI: 10.1002/etc.3808
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic potential of undispersed and dispersed fresh and weathered Macondo crude oils to Gulf of Mexico Marine Organisms

Abstract: Crude oils contain a mixture of hydrocarbons, including phototoxic polycyclic aromatic hydrocarbons (PAHs) that have the ability to absorb ultraviolet (UV) light. Absorption of UV light by PAHs can substantially increase their toxicity to marine organisms. The objective of the present study was to examine the potential for phototoxicity of fresh and naturally weathered Macondo crude oils alone and in combination with the dispersant Corexit 9500 to mysid shrimp (Americamysis bahia), inland silverside (Menidia b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…There was less than 10% mortality of zebrafish larvae in the water-only control and the two dispersant-only treatments, including the 100% sunlight exposures, indicating a lack of phototoxicity in the absence of oil. These results are consistent with other studies showing that dispersants alone are not phototoxic to aquatic organisms Alloy et al 2017;Finch et al 2017;Sweet et al 2017). There was 0% survival of fish exposed to 100% solar radiation in the oil WAF high and CEWAF high treatments, which were significantly different from the almost complete survival of larvae exposed to 10% solar radiation (chi-square ≥ 4.5; p-value ≤ 0.03; Fig 1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There was less than 10% mortality of zebrafish larvae in the water-only control and the two dispersant-only treatments, including the 100% sunlight exposures, indicating a lack of phototoxicity in the absence of oil. These results are consistent with other studies showing that dispersants alone are not phototoxic to aquatic organisms Alloy et al 2017;Finch et al 2017;Sweet et al 2017). There was 0% survival of fish exposed to 100% solar radiation in the oil WAF high and CEWAF high treatments, which were significantly different from the almost complete survival of larvae exposed to 10% solar radiation (chi-square ≥ 4.5; p-value ≤ 0.03; Fig 1).…”
Section: Resultssupporting
confidence: 92%
“…There have been relatively few studies of the photoenhanced toxicity of chemically dispersed oil since the first report by . Recently, studies with fish and invertebrate species native to the Gulf of Mexico have confirmed the phototoxicity of chemically dispersed oil from the Deepwater Horizon spill in laboratory water exposures (Alloy et al 2017;Finch et al 2017;Sweet et al 2017).…”
mentioning
confidence: 98%
“…For the petroleum phototoxicity assessment, 4 species indigenous to the Gulf of Mexico, including A. bahia , M. beryllina , C. variegatus , and F. grandis were exposed to 3 field‐collected oils. Natural sunlight (Supplemental Data, Worksheet 2, Table WS2‐15 for the full spectrum), solar‐simulated light (Supplemental Data, Worksheet 2, Table WS2‐15 for the full spectrum), and no light exposure studies were conducted with exposure concentrations of 100, 25, and 6.25% WAF . The CTLBBs for A. bahia , M. beryllina , and C. variegatus are from the literature .…”
Section: Methodsmentioning
confidence: 99%
“…Weathering of oil removes lighter PAH compounds (1-2 rings), while retaining heavier PAHs, some of which are known to be phototoxic (3-5 rings; Riley et al 1980;Barron et al 1999). Several crude oils have been demonstrated to be phototoxic (Cleveland et al 2000; Barron et al 2003) including Macondo crude oil (Alloy et al 2015;Finch et al 2017). Macondo crude oils contain significant concentrations of phototoxic PAHs (Finch et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several crude oils have been demonstrated to be phototoxic (Cleveland et al 2000; Barron et al 2003) including Macondo crude oil (Alloy et al 2015;Finch et al 2017). Macondo crude oils contain significant concentrations of phototoxic PAHs (Finch et al 2017). Finch et al (2016Finch et al ( , 2017 reported increased toxicity to mysid shrimp, inland silverside, and Pacific and eastern oyster larvae exposed to weathered Macondo crude oil water accommodated fractions (WAFs) in the presence of sunlight.…”
Section: Introductionmentioning
confidence: 99%